Research and implementation of HTAP for distributed database - Jing, Changhong; Liu, Wenjie; Gao, Jintao; Pei, Ouya (Xibei Gongye Daxue Xuebao, 2021)
Data processing can be roughly divided into two categories, online transaction processing OLTP(on-line transaction processing) and online analytical processing OLAP(on-line analytical processing). OLTP is the main application of traditional relational databases, and it is some basic daily transaction processing, such as bank pipeline transactions and so on. OLAP is the main application of the data warehouse system, it supports some more complex data analysis operations, focuses on decision support, and provides popular and intuitive analysis results. As the amount of data processed by enterprises continues to increase, distributed databases have gradually replaced stand-alone databases and become the mainstream of applications. However, the current business supported by distributed databases is mainly based on OLTP applications, lacking OLAP implementation. This paper proposes an implementation method of HTAP for distributed database CBase, which provides an implementation method of OLAP analysis for CBase, and can easily deal with data analysis of large amounts of data. 数据处理可大致分为2类，联机事务处理OLTP（on-line transaction processing）和联机分析处理OLAP（on-line analytical processing）。OLTP是传统关系型数据库的主要应用，支持一些基本的日常的事务处理，如银行流水交易等。OLAP是数据仓库系统的主要应用，支持一些较为复杂的数据分析操作，专注于决策支持，提供出通俗直观的分析结果。随着企业处理数据量的不断增加，分布式数据库已经逐渐取代单机数据库，成为应用的主流。但目前分布式数据库支持的业务主要以OLTP应用为主，缺少OLAP实现。提出了一种面向分布式数据库CBase的HTAP的实现方法，为CBase提供了一种OLAP分析的实现方式，可以轻松应对大数据量的数据分析。